The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ijn.s244743
|View full text |Cite|
|
Sign up to set email alerts
|

<p>A Cleverly Designed Novel Lipid Nanosystem: Targeted Retention, Controlled Visual Drug Release, and Cascade Amplification Therapy for Mammary Carcinoma in vitro</p>

Abstract: Objective: To construct an ideal theranostic nanoplatform (LIP3); to clarify its physicochemical properties; to confirm its characteristics of dual-modality imaging, active-targeting, and cascade amplification therapy for mammary carcinoma; and to perform a preliminary exploration of the cytotoxicity mechanism. Design: A self-prepared liposome nanosystem, LIP3, can actively target 4T1 cells because the surface is linked with C-RGD. Haematoporphyrin monomethyl ether (HMME), an excellent sonosensitizer entrapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The liposomes were synthesized using a two-step emulsion method. 31 Transmission electron microscopy demonstrated a nearly spherical structure of lip-ICG-PFP and Lip-ICG-PFP-cRGD with smooth surfaces (Figs. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…The liposomes were synthesized using a two-step emulsion method. 31 Transmission electron microscopy demonstrated a nearly spherical structure of lip-ICG-PFP and Lip-ICG-PFP-cRGD with smooth surfaces (Figs. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown that LIFU could enhance the drug sensitivity of some select chemotherapeutic drugs and could improve cell membrane permeability [ 33 35 ]. Our previous research showed that the combination of LIFU exposure and the nanobubble system can be used as an efficient and safe approach for gene delivery and transfection [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of ROS during this process induces cytotoxicity toward cancer cells effectively, leading to rapid DNA damage and apoptosis of tumor cells [9]. Unlike the super cial employment of photodynamic therapy (PDT), SDT receives a more pleasant therapeutic outcome in treating deep-seated tumors by low intensity focused ultrasound (LIFU) which owns merits to prevent undesirable thermal injury during treatment [11][12][13]. As one of the essentials in SDT, sonosensitizers have been explored in various tumor therapies [14].…”
Section: Introductionmentioning
confidence: 99%